An In Vitro Brain Tumour Model in Organotypic Slice Cultures Displaying Epileptiform Activity - Harvey K. Chong; Ziang Ma; Kendrew Ka Chuon Wong; Andrew Morokoff; Chris French (Brain Sciences, 2023)
Brain tumours have significant impacts on patients’ quality of life, and current treatments have limited effectiveness. To improve understanding of tumour development and explore new therapies, researchers rely on experimental models. However, reproducing tumour-associated epilepsy (TAE) in these models has been challenging. Existing models vary from cell lines to in vivo studies, but in vivo models are resource-intensive and often fail to mimic crucial features like seizures. In this study, we developed a technique in which normal rat organotypic brain tissue is implanted with an aggressive brain tumour. This method produces a focal invasive lesion that preserves neural responsiveness and exhibits epileptiform hyperexcitability. It allows for real-time imaging of tumour growth and invasion for up to four weeks and microvolume fluid sampling analysis of different regions, including the tumour, brain parenchyma, and peritumoral areas. The tumour cells expand and infiltrate the organotypic slice, resembling in vivo behaviour. Spontaneous seizure-like events occur in the tumour slice preparation and can be induced with stimulation or high extracellular potassium. Furthermore, we assess extracellular fluid composition in various regions of interest. This technique enables live cell confocal microscopy to record real-time tumour invasion properties, whilst maintaining neural excitability, generating field potentials, and epileptiform discharges, and provides a versatile preparation for the study of major clinical problems of tumour-associated epilepsy.